Strengths and challenges with spiritual care: Student feedback from the EPICC Spiritual Care Self‐Assessment Tool - Pamela H. Cone; Joanne Lassche‐Scheffer; Bodil Bø; Britt Moene Kuven; Wilfred McSherry; Benson Owusu; Linda Ross; Annemiek Schep‐Akkerman; Venke Ueland; Tove Giske (Wiley, 2023)
Abstract Aim To explore qualitative data from students' self‐reported competencies in spiritual care gathered during testing of a student self‐assessment tool based on the EPICC Spiritual Care Education Standard. Design Reflexive thematic analysis of qualitative data from a multinational study on validating a new self‐assessment tool. Methods The EPICC Spiritual Care Education Standard for competency in spiritual care was developed to enhance nurses' and midwives' ability to provide spiritual care by creating a baccalaureate education standard for spiritual care competencies. Spiritual care researchers then developed a self‐assessment tool to raise student awareness of spirituality and track personal and professional growth in spiritual care competency. The EPICC Spiritual Care Competency Self‐Assessment Tool, tested at eight universities in five countries, provided many opportunities for student comments, resulting in rich qualitative data presented here. Results Themes related to strengths, weaknesses and areas for improvement. Identified strengths were similar across countries: caring attitudes, general knowledge of caring and compassion and good communication skills. Weaknesses/challenges touched on spirituality as overlooked in some cultures but part of life for others, complex questions were hard to understand, and self‐assessment tools are common for some and rare for others. Areas for improvement included need for knowledge of religious and other deeply held beliefs and for greater spiritual assessment skills. Similarities across countries related to basic training in communication and compassionate care for nurses globally. Differences lay in the challenges and/or barriers for spiritual care and may relate to cultures within countries and/or university test sites. Relevance to clinical practice The Tool raises awareness of spirituality among students and working nurses, providing an accessible way to self‐check personal and professional growth in spiritual care competencies, which increases student and nurse capacity to become more knowledgeable and skilled in facilitating spiritual care, thus be role models for students at the intersection of spirituality and health.